Measurement and Correlation of Indices of Insulin Resistance in Patients on Peritoneal Dialysis. Issue 4 (July 2016) - King-Morris, Kelli R.; Deger, Serpil Muge; Hung, Adriana M.; Egbert, Phyllis Ann; Ellis, Charles D.; Graves, Amy; Shintani, Ayumi; Ikizler, T. Alp
Background: Insulin resistance (IR) is common in maintenance dialysis patients and is associated with excess mortality. Hyperinsulinemic euglycemic glucose clamp (HEGC) is the gold standard for measuring IR. There are limited studies using HEGC for comparison to other indirect indices of IR in peritoneal dialysis (PD) patients, nor have there been direct comparisons between patients receiving PD and those on maintenance hemodialysis (MHD) with regard to severity of IR, methods of measurement, or factors associated with the development of IR. Methods: This is a cross-sectional, single-center study performed in 10 prevalent PD patients of median age 48 years (range 41 – 54); 50% were female and 60% were African American. Insulin resistance was assessed by HEGC (glucose disposal rate [GDR]), homeostatic model assessment of IR (HOMA-IR), HOMA-IR corrected by adiponectin (HOMA-AD), leptin adiponectin ratio (LAR), quantitative insulin sensitivity check index (QUICKI), McAuley's index, and oral glucose tolerance test (OGTT) at each time point for a total of 18 studies. Retrospective analysis compared this cohort to 12 hemodialysis patients who had previously undergone similar testing. Results: The median GDR was 6.4 mg/kg/min (interquartile range [IQR] 6.0, 7.8) in the PD cohort compared with the MHD group, which was 5.7 mg/kg/min (IQR 4.3, 6.6). For both the PD and MHD cohorts, the best predictors of GDR by HEGC after adjusting for age, gender, and body mass index (BMI), were HOMA-AD (PD: r = -0.69, p = 0.01; MHD: r = -0.78, p = 0.03) and LAR (PD: r = -0.68, p < 0.001; MHD: r = -0.65, p = 0.04). In both groups, HOMA-IR and QUICKI failed to have strong predictive value. Eight of 10 PD patients had at least 1 abnormal OGTT, demonstrating impaired glucose tolerance. Conclusions: Insulin resistance is highly prevalent in PD patients. The adipokine based formulas, HOMA-AD and LAR, correlated well in both the PD and MHD populations in predicting GDR by HEGC, outperforming HOMA-IR. The use of these novel markers could be considered for large-scale, epidemiological outcome studies.